Development of a protocol for fire testing of columns - Tan, Kevin C.
Fire testing is perfonned to study the behavior and performance of building components when exposed to fire. ill a fire test, a test specimen is placed in a funlace and exposed to extreme heat, simulating actual fire conditions. The loading frame or restraint frame is an important piece of equipment in a furnace where the test specimen of structural member is placed prior to being tested. It supports the test setup used to apply the proper loading, boundary conditions and restraint to simulate the conditions experienced by the member during a fire. The Institute of Civil Engineering, College of Engineering, University of the Philippines, Diliman is currently bnilding a fire testing laboratory; however, its fire testing furnace does not yet have a finalized design for a loaded restraint frame. The standards, unfortunately, do not specify how to design a loading frame. In addition, many existing joumals and studies involving fire testing do not explain in detail how they designed the loading frame they used in their experiments. The objectives of this thesis are: firstly to design a loading frame, and secondly to develop a protocol for fire testing of columns. This study analyzed the setups used in other experiments and used them as a guide for designing a loading frame applicable to the furnace in the Institute's fire testing laboratory. The proposed schematic design has three hydraulic jacks applying loads from the top through a horizontal loading beam. It is capable of applying a total of a 100-ton axial load on the test column from the top. In addition, it can also apply different magnitudes of bending stresses by combinations of loads of the hydraulic jacks. For the second objective, a protocol was developed based on the guidelines set by intemational standards, specifically ASTM E119, BS 476, BS EN 1363 and ISO 834. It includes only the parts that are applicable to the furnace in the Institute's fire testing laboratory. The proposed protocol is not meant to be the sole reference in conducting a fire test. Instead, it is meant to serve as a guide for users to better understand fire testing practices and equipment, and guide them in designing their own experimental programs. The fire testing standards are constantly being revised and updated, and it is recommended that as soon as new standards are available, the protocol be revised accordingly.